Pelatihan Multimedia Interaktif Berbantuan Aplikasi Assembler Edu Kepada Guru-Guru SMP - Alfa Mitri Suhara; R. Mekar Ismayani (IKIP SILIWANGI, 2024)
The Covid-19 pandemic, which has not yet ended, has an impact on the implementation of learning, which still applies the learning process from home for several areas that are still at level 3. Therefore, teachers must continue to improve their abilities and creativity in managing an interesting learning process. Integrating technological advances by utilizing them in learning, especially for teachers in designing teaching materials or learning media that are multimedia and interactive is urgently needed. Many platforms or applications that can be utilized. One such application is Assembelr Edu. The results of initial observations show that not all teachers use the application in the learning process. This is due to limited information. Thus, a training is needed for teachers to be better prepared in carrying out distance learning. This PKM activity is in collaboration with partners, in this case SMP Kartika XIX-1 Bandung in the form of training and guidance on making interactive multimedia with the help of the Assemblr Edu application. This training activity was carried out by providing first, socialization and delivery of material. Second, direct training through mentoring and instructor guidance in making interactive multimedia with the help of the Assemblr Edu application. Third, the teacher simulates the multimedia that has been made in front of the other participants. In addition, feedback and follow-up plans will be carried out to find out the students' responses to the multimedia.